EFFICIENT FLOATING POINT FAST FOURIER TRANSFORM BUTTERFLY ARCHITECTURE USING BINARY SIGNED DIGIT MULTIPLIER AND ADDERS - Acharya, Shivani; Beulet, Augusta Sophy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Fast Fourier transform (FFT) is one of the most important tools in digital signal processing as well as communication system because transforming time domain to S-plane is very convenient using FFT. As FFT uses various techniques to convert a signal from time domain to S-domain and inverse, out of which butterfly technique is the one on which paper is focused on. Butterfly technique uses additions and multiplications of operands to get the required output. Floating point (FP) is used as operands due to their flexibility. As the computations involving FP has less speed, we have used binaryÂ signed digit (BSD). BSD will take the less time for addition and subtraction. Three bit BSD adder and FP adder together will make a fused dot product add (FDPA) unit. In FDPA, unit addition and subtraction will be one group and multiplication will be one group and then their respective results will be fused. Modified booth encoding and decoding algorithm are used here to make the complex multiplication with ease. Â